1989
DOI: 10.1002/jlac.198919890294
|View full text |Cite
|
Sign up to set email alerts
|

Gloeosporone – A Macrolide Fungal Germination Self‐Inhibitor Total Synthesis and Activity

Abstract: Starting with (S)‐ or (R)‐4‐Bromo‐1,2‐epoxybutane [commercially available or readily made from (S)‐ or (R)‐malic acid], both enantiomers of the germination self‐inhibitor gloeosporone were synthesized. The absolute configuration of the natural product was thus proven to be 4S,7R,13R. Microbiological studies showed that both enantiomers of the compound cause inhibition of germination in spores of Colletotrichum gloeosporioides, and that (‐)‐gloeosporone is also active against a variety of other fungi. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Next, the Wittig-salt 7 was synthesized. The dianion of 4-pentynoic acid (11) in HMPA, 21 prepared by treatment with excess n-BuLi, was reacted with ethylene oxide (10). This afforded 7-hydroxy-hept-4-ynoic acid which was directly esterified to 18 (MeOH, catalytic H 2 SO 4 ), see Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the Wittig-salt 7 was synthesized. The dianion of 4-pentynoic acid (11) in HMPA, 21 prepared by treatment with excess n-BuLi, was reacted with ethylene oxide (10). This afforded 7-hydroxy-hept-4-ynoic acid which was directly esterified to 18 (MeOH, catalytic H 2 SO 4 ), see Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…12 Various synthetic studies have been reported. [13][14][15][16][17][18][19] The structures of the major metabolites of C. gloeosporioides are shown in Fig. 1.…”
Section: Metabolites Isolated From Colletotrichum Gloeosporioidesmentioning
confidence: 99%
“…As shown in Table 1, the number of atoms in the targeted ring is not as important as two other variables. When the ring size was kept constant but the number of CH 2 groups between the ester and alkyne was varied, the superiority of three CH 2 units (n = 1) versus two or four such units was observed (n = 0 or 2, respectively; Table 1, entries [1][2][3][4][5][6]. With this requirement satisfied, 12-and 15-membered rings could also be prepared in this fashion, albeit with reduced efficiency ( Table 1, entries 7-10).…”
mentioning
confidence: 99%